2014
DOI: 10.5897/ijsa2013.0494
|View full text |Cite
|
Sign up to set email alerts
|

Childs growth and nutritional status in two communities-Mishing tribe and Kaibarta caste of Assam, India

Abstract: Physical growth and development studies were carried out among the populations of both tribal and non-tribal in eastern India by different scholars in different milieu and environmental factors from the eighties and onwards. Since then, the inhabitants of those areas have been doing agriculture, fishing, etc as prime occupation, but after a few decades in the same region, demographic and socioeconomic changes took place under the influences of worldwide globalization of industrialization. These are evident in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A study on growth and nutritional status of 3 to 10 year-old children from two communities, e.g. Mishing (a scheduled tribe) and Kaibarta (a scheduled caste of Hindus) of Assam State in northeast India [17] recorded higher prevalence of stunting in boys (Mishing 26.84%, Kaibarta 33.33%) than girls (Mishing 21.31%, Kaibarta 18.06%). In Tripura, another north-eastern state, rural boys aged 8 to 15 years were also found to experience high degree stunting (28%) than urban age-peers (8%) [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on growth and nutritional status of 3 to 10 year-old children from two communities, e.g. Mishing (a scheduled tribe) and Kaibarta (a scheduled caste of Hindus) of Assam State in northeast India [17] recorded higher prevalence of stunting in boys (Mishing 26.84%, Kaibarta 33.33%) than girls (Mishing 21.31%, Kaibarta 18.06%). In Tripura, another north-eastern state, rural boys aged 8 to 15 years were also found to experience high degree stunting (28%) than urban age-peers (8%) [11].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that around 84% boys and 47% girls were stunted. Studies among children and adolescents from tribal communities also reported high prevalence of stunting from eastern and north-eastern India [17,18,19,20,21]. However, compared to the studies carried out in the communities living in urban and rural areas of India, reports from underprivileged sections of the society especially the tribal communities are relatively less.…”
Section: Introductionmentioning
confidence: 98%